Joint Impact Assessment of CTA's support to CaFAN (2004-2012) - Scott, Cleve; Munro, Shantal (Technical Centre for Agricultural and Rural Cooperation, 2020)
The Caribbean Farmers Network Inc. (CaFAN) is a registered not-for-profit organisation representing about 500,000 small-scale farmers in 15 Caribbean countries. The organisation’s secretariat is located in Kingstown, St. Vincent and the Grenadines. CaFAN conducted this joint impact study, commissioned by the Technical Centre for Agricultural and Rural Cooperation (CTA), to examine in-depth the impact of CTA funding and programme support to CaFAN. The findings are to contribute to learning for development impact within CTA and its ACP partner organisations and networks.